2021
DOI: 10.1007/s10664-020-09930-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient static analysis and verification of featured transition systems

Abstract: A Featured Transition System (FTS) models the behaviour of all products of a Software Product Line (SPL) in a single compact structure, by associating action-labelled transitions with features that condition their presence in product behaviour. It may however be the case that the resulting featured transitions of an FTS cannot be executed in any product (so called dead transitions) or, on the contrary, can be executed in all products (so called false optional transitions). Moreover, an FTS may contain states f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Feature dependencies may cause anomalies such as atomic-sets-i.e., sets of features that must either be all active or all inactive at the same time-and dead features-that can never be active in any valid configuration. Such anomalies can be detected and refactored to improve the quality of a FM; this is an active research area and includes structural [5] and behavioral [4] approaches. In addition to FOP, other paradigms for SPLE such as aspect-oriented programming (AOP) [15] and delta-oriented programming (DOP) [32] exist.…”
Section: Software Product Linesmentioning
confidence: 99%
“…Feature dependencies may cause anomalies such as atomic-sets-i.e., sets of features that must either be all active or all inactive at the same time-and dead features-that can never be active in any valid configuration. Such anomalies can be detected and refactored to improve the quality of a FM; this is an active research area and includes structural [5] and behavioral [4] approaches. In addition to FOP, other paradigms for SPLE such as aspect-oriented programming (AOP) [15] and delta-oriented programming (DOP) [32] exist.…”
Section: Software Product Linesmentioning
confidence: 99%
“…This may seem computationally expensive. However, it has been shown that static analysis of properties of fTSs that concern the reachability of states and transitions in valid products (LTSs) is feasible in reasonable time even for fTSs of considerable size, by reducing the analysis to SAT solving [7]. In fact, while SAT solving is NP-complete, SAT solvers are effectively used for static analysis of feature models with hundreds of thousands of clauses and tens of thousands of variables [32,31].…”
Section: Note On Complexitymentioning
confidence: 99%
“…This may seem computationally expensive. However, it has been shown that static analysis of properties of fTSs that concern the reachability of states and transitions in valid products (LTSs) is feasible in reasonable time even for fTSs of considerable size, by reducing the analysis to SAT solving [7]. In fact, while SAT solving is NP-complete, SAT solvers are eectively used for static analysis of feature models with hundreds of thousands of clauses and tens of thousands of variables [32,31].…”
Section: 3mentioning
confidence: 99%